Penerapan Rank Reciprocal dan Multi-Attributive Border Approximation Area Comparison Untuk Penentuan Lokasi Cafe Baru - Sanriomi Sintaro (PT. Tech Cart Press, 2024)
Determining the location for a new café involves careful and strategic considerations to ensure the success of the business. Geographical aspects such as local population, demographics, and level of competition in the area are the main factors considered. The combination of careful analysis of geographical factors, markets, as well as branding and business concepts, will help in determining the optimal location to open a successful new café. This study aims to provide recommendations for new café locations by applying a decision support system model, namely the reciprocal rank method to determine the weight of criteria and MABAC to assess the location of new cafes so that it will produce ranking recommendations for new locations. The application of reciprocal rank and MABAC methods in determining the location of new businesses gets the final results and provides recommendations for rank 1 with a final value of 0.4792 obtained by Location A, rank 2 with a final value of 0.2552 obtained by Location T, and rank 3 with a final value of 0.1512 obtained by Location D.